Prevalence and sociodemographic factors of risky drinking in Australian older adults. (23rd July 2020) - Jiang, Heng; Griffiths, Susan; Callinan, Sarah; Livingston, Michael; Vally, Hassan
Abstract: Introduction and Aims: This study describes the prevalence of risky drinking in older adults (aged 60+ years) in Australia and explores the socioeconomic and lifestyle factors associated with this. The negative consequences of drinking behaviours in older adults were also explored. Design and Methods: Cross‐sectional design, with data obtained from the Australian 2016 National Drug Strategy Household Survey, yielding a sample size of 7976 participants. Multivariable logistic regression was used to assess the correlates of risky drinking. Results: Approximately 17% of older Australians reported risky drinking and their most popular drinking location was in the home (93%). Respondents who were male [odds ratio 3.78, 95% confidence interval (3.22, 4.43)], of younger age group (60–69 years) [2.96, (2.25, 3.89)], in a higher socioeconomic status [1.76, (1.41, 2.21)], had no dependents [1.51, (1.10, 2.07)], were unemployed [1.64, (1.10, 2.44)] and were either current or ex‐smokers [2.32, (1.90, 2.83) or 3.55, (2.95, 4.29)], were more likely to report risky drinking. Approximately 54% of risky drinkers experienced a negative outcome as a result of their drinking in the last year. Discussion and Conclusions: Risky drinking in older adults is a key public health issue, with a concerning rate of risky drinking and associated negative outcomes seen in the current study. Interventions aimed at older drinkers thus need to focus beyond socio‐economically disadvantaged groups, while self‐moderation on risky drinking, controlling accessibility to take‐away alcohol and increasing the awareness of harms of risky drinking may help to reduce risky drinking among older people.